2004
DOI: 10.1128/iai.72.3.1223-1229.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of MyD88 in Diminished Tumor Necrosis Factor Alpha Production by Newborn Mononuclear Cells in Response to Lipopolysaccharide

Abstract: Human newborns are more susceptible than adults to infection by gram-negative bacteria. We hypothesized that this susceptibility may be associated with a decreased response by leukocytes to lipopolysaccharide (LPS). In this study, we compared LPS-induced secretion of tumor necrosis factor alpha (TNF-␣) by mononuclear cells (MNC) from adult peripheral blood and newborn umbilical cord blood in vitro and attempted to determine the mechanisms involved in its regulation. At a high concentration of LPS (10 ng/ml) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
115
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(133 citation statements)
references
References 51 publications
(41 reference statements)
11
115
1
5
Order By: Relevance
“…Whether and how the innate immune response in neonates contributes to their susceptibility to infection or TLR stimulation is still controversial. In human, it has been reported that mononuclear cells from cord blood secrete lower amounts of TNF than those from healthy adults in response to TLR agonists (10)(11)(12)(13), whereas other studies draw opposite conclusions (14)(15)(16). Results from studies in mice also conflict because neonates produce either lower (17,18) or higher (19) levels of TNF compared with adults.…”
contrasting
confidence: 38%
“…Whether and how the innate immune response in neonates contributes to their susceptibility to infection or TLR stimulation is still controversial. In human, it has been reported that mononuclear cells from cord blood secrete lower amounts of TNF than those from healthy adults in response to TLR agonists (10)(11)(12)(13), whereas other studies draw opposite conclusions (14)(15)(16). Results from studies in mice also conflict because neonates produce either lower (17,18) or higher (19) levels of TNF compared with adults.…”
contrasting
confidence: 38%
“…Although neonatal monocytes express similar levels of mRNA for different TLRs than adult monocytes [20,19], these data do not exclude possible differences in the protein expression of such receptors. Some data also support a defect in TLR signaling: (1) the up-regulation of TLR4 and CD14 expression upon LPS stimulation is not observed in neonatal monocytes [19,21]; and (2) the protein expression of MyD88, an important adaptor molecule involved in TLR-mediated signaling, is decreased in neonatal monocytes [21], although MyD88 mRNA levels are similar in neonatal and adult monocytes [19]. It should be noted that the expression of several key molecules involved in TLR signaling, such as TIRAP and IRAK-4, has not been carefully examined.…”
Section: Neonatal Monocytes and Macrophagesmentioning
confidence: 99%
“…Even in the case of LPS, where several studies have explored the relative responses of newborn and adult cells (17), much of the published work was performed before the realization that commercial preparations of LPS are often contaminated with TLR2 ligands (18). A recent study described a correlation between reduced responsiveness of newborn mononuclear cells to LPS and reduced MyD88 expression (19). However, to our knowledge, there are no published reports of the activity of a range of well-defined TLR ligands and expression of their cognate receptors and signaling intermediates in newborn monocytes.…”
mentioning
confidence: 99%